Risk Factors of Intra-familial Hepatitis B Virus Transmission among Hepatitis B Patients in Kupang, Indonesia - Norma Tiku Kambuno; Meylani Fernanda Bessie; Marni Tangkelangi; Agustina Welhelmina Djuma (Global Medical & Health Communication (GMHC), 2019)
Hepatitis B is caused by acute or chronic hepatitis B virus infection. It is the most dangerous liver disease compared to other liver diseases due to its lack of apparent symptoms. The symptoms include slight jaundice in the eyes and skin accompanied by lethargy. This study aimed to determine the risk factors for intra-familial transmission of hepatitis B virus for household contacts of hepatitis B patients. The analytical correlation study with a cross-sectional design was conducted from June to July 2018 in Alak subdistrict, Kupang, Indonesia. Venous blood was collected from 45 subjects consisting of 12 patients and 33 family member. Examination was then performed using HBsAg test strip, resulting in the percentage of transmission of 15.15%. Statistical analysis revealed p>0.05. In conclusions, no relationship between gender, age, education, marital status, occupation, and HBsAg status. These characteristics are not risk factors for conversion of HBsAg status. FAKTOR RISIKO PENULARAN VIRUS HEPATITIS B KONTAK SERUMAH DI ANTARA PASIEN HEPATITIS B DI KUPANG, INDONESIAHepatitis B disebabkan oleh infeksi virus hepatitis B yang bersifat akut atau kronik. Penyakit ini termasuk penyakit hati yang paling berbahaya dibanding dengan penyakit hati yang lain karena tidak menunjukkan gejala yang jelas. Gejalanya hanya sedikit warna kuning pada mata dan kulit disertai lesu. Penelitian ini bertujuan mengetahui faktor risiko penularan virus hepatitis B pada kontak serumah pasien hepatitis B. Penelitian korelasi analitik dengan desain cross-sectional ini dilaksanakan pada bulan Juni sampai Juli 2018 di Kecamatan Alak, Kupang, Indonesia. Darah vena diambil dari 45 subjek yang terdiri atas 12 pasien dan 33 anggota keluarga. Pemeriksaan kemudian dilakukan menggunakan strip tes HBsAg menghasilkan persentase penularan 15,15%. Analisis statistik didapatkan p>0,05. Simpulan, tidak terdapat hubungan antara jenis kelamin, usia, pendidikan, status pernikahan, pekerjaan, dan status HbsAg. Karakteristik ini bukan faktor risiko untuk konversi status HBsAg.